Geochemistry of Early Devonian calc-alkaline plutons in the Merrimack Belt: implications for mid-Paleozoic terrane relationships in the New England Appalachians - Watts, Brandon; Dorais, Michael; Wintsch, Robert (Atlantic Geology, 2000)
A series of northeast-trending plutons extending from northeastern Massachusetts to southeastern Maine intruded the metascdimenlary rocks of the Merrimack belt. The Early Devonian Oacut, Sweepstakes, Island Pond. Exeter, and Wcbhannet plutons are metaluminous and, with the exception of the granitic Webhannet pluton, are dominantly mafic to intermediate in composition. The plutons are calc-alkaline in character and have major, minor, and trace clement compositions typical of magmas generated at destructive plate margins. These characteristics include mid- to high-K contents, enrichment of LII.E, LREE, Ba. and Sr, and negative Nb and Ta anomalies. Whole-rock chemical data indicate that the plutons of the Merrimack belt arc similar in every measured geochemical parameter to ca. 400 Ma mafic to intermediate rocks of the New Hampshire Plutonic Suite. These similarities suggest that both groups of plutons were emplaced within the same magmatic arc and belong to the same magmatic suite. A magmatic suite common to both the Merrimack belt and Central Maine terrane suggests that the two lithotcctonic zones were proximal to each other at ca. 400 Ma. Trace element differences between Merrimack belt and Sharpners Pond rocks suggest (hat the Putnam-Nashoba terrane represents a separate arc. Located in the Central Maine terrane of New Hampshire, the Rochester pluton is geochemically distinct from the Siluro-Devonian plutons of the Merrimack belt and New Hampshire Plutonic Suite. The Rochester pluton has alkaline affinities but retains overall calc-alkaline features. High concentrations of incompatible elements (K, Ti. P. Ba. Rb, Zr) in the Rochester pluton are markedly similar to those observed in the 360 Ma Hardwick Tonalitc of Massachusetts. The strong geochemical correlation between the Rochester and Hardwick plutons implies derivation from the same magmatic event and a common, Late Devonian origin. We suggest that these plutons may have originated in response to pull-apart rifting related to late-stage Acadian transpression.